Implementasi Perpres No. 7 Tahun 2021 Tentang Rencana Aksi Nasional Pencegahan Dan Penanggulangan Ekstremisme Berbasis Kekerasan Yang Mengarah Pada Terorisme (Ran Pe) Di Tingkat Desa: Analisis Kebijakan Dan Tantangan - Mahendra, Husaini Damar; Kemala, Anyelir Puspa (Postulat, 2024)
On January 6, 2021, the Indonesian government officially issued Presidential Regulation No. 7 of 2021 on the National Action Plan for the Prevention and Countering of Violent Extremism Leading to Terrorism (RAN PE) as a legal basis for addressing terrorism in Indonesia. This regulation imposes an obligation on the state to provide a sense of security for Indonesian citizens and to maintain national security stability. It’s implementation faces unique challenges due to Indonesia’s diverse regional characteristics. This presents a challenge for the Indonesian government to successfully implement the RAN PE Presidential Regulation. The author conducted research on the policies enacted by local government officials, such as Village Chiefs, Bhabinkamtibmas (Community Police Officers), Babinsa (Military Supervisors), and Religious Counselors, regarding the implementation of Presidential Regulation No. 7 of 2021 and the challenges encountered. The research method used in this journal is qualitative and descriptive.